Tingkat Akseptabilitas dan Tolerabilitas Cairan Pencuci Tangan Formula World Health Organization (WHO) yang Digunakan Mahasiswa Kepaniteraan Klinik Senior di RSUD Arifin Achmad Provinsi Riau - Dewi Anggraini; Insan Fitriyani; Tuti Restuastuti (Fakultas Kedokteran Universitas Riau, 2015)
Health Care Associated Infection (HCAI) is one of the leading cause of mortality and morbidity in hospital and otherhealth care facilitiy. Hand hygiene is the main way to reduce incidence of HCAI. World Health Organization (WHO)recommends alcohol-based handrub because it is more acceptable and tolerable than other hand hygiene products.WHO has identified formulations for the local preparation. This was a descriptive study aimed to determine theacceptability and tolerability of WHO recommended handrub formulation. The subjects of the study were 40 seniorclerkships in Arifin Achmad Hospital, Riau Province, from Surgery, Obstetrics and Gynecology, and Internal MedicineDepartment. Each respondent was given WHO-recommended handrub formulation used for three days. On the firstday, the observer distributed handrubs being tested. After 3 days of consecutive use of the product, participantscompleted the questionnaire and the observer evaluate the condition of participants’ hands. We used WHO’squestionnaire to evaluate acceptability and tolerability level. The results of this study showed that WHO-recommendedhandrub formulation had good acceptability for its application, colour, smell, irritation, ease of use, speed of drying,and overall evaluation but had a less rate of acceptability for its textures and drying effect. WHO-recommendedhandrub formulation had good tolerability.